Hubungan Hasil Belajar Mata Pelajaran Dasar Kecantikan Dengan KesiapanKerja Siswa Jurusan Tata Kecantikan Smk Negeri 3 Payakumbuh Dalam Melaksanakan Praktik Kerja Industri. - Sab, Puteri Gemasih (journal of residu, 2019)
The cause of the unpreparedness of students to carry out industrial field practice is strongly influenced by student learning outcomes, preliminary surveys when carrying out practices of students majoring in beauty in Basic Beauty Skin and Hair students still look awkward in carrying out practices, feeling burdened by spending on buying practical tools that are not available at school and students are still not ready to carry out the tasks given. This is because students are not sure of their abilities. This study aims to a) work readiness, b) learning outcomes, c) the relationship between the learning outcomes of Basic Beauty subjects and the readiness of student work. This type of research is quantitative descriptive with a correlational approach. This research was conducted at SMK N 3 Payakumbuh from August to September. The population in this study were students of the Department of Skin and Hair Beauty at SMK Negeri 3 Payakumbuh in the academic year 2018 / 2019-2019 / 2020 as many as 63 students, the sampling technique was total sampling. The data collection technique is using a questionnaire adjusted in the form of a Likert scale that has been tested for validity and reliability. The data analysis technique uses the correlation coefficient test followed by the t test for the analysis of the significance of the correlation coefficient. Based on the results of data analysis states that industrial work readiness is in the medium category with a percentage of 79.36%, where the affective readiness aspect (attitude) is in the moderate category with a percentage of 76.67%, the psychomotor readiness aspect (skills) in the good category with a percentage of 81,60%.Of the 63 students there were 32 students (50.8%) who had learning outcomes <77.78 with incomplete categories and 31 students (49.2%) had learning outcomes> 77.78 with complete categories.Correlation analysis results obtained r count value of 0.410 with a fairly strong interpretation of the relationship with a sig value of 0,000 <0.05.Correlation test is obtained by t count> t table (76.106> 1.998) which means that Ha is accepted. It is recommended to teachers to further enhance student work readiness through efforts to improve the quality of teaching and learning process and to complete the facilities and infrastructure of student learning.